A bibiliometric analysis of the Journal of Infection and Public Health: 2008-2016 - Erwin Krauskopf (Elsevier, 2018)
Background: The Journal of Infection and Public Health published its first issue in 2008. The fact that the journal has been published uninterruptedly as well as its editorial content and the application of a peer-review process to select manuscripts, made the journal eligible to be indexed by databases such as Scopus. This study presents a general overview of the journal from 2008 until 2016 using bibliometric indicators to assess its performance. Methods: The data for this study, dating between 2008 and 2016, was extracted from Scopus database. All the information was exported in CSV format to the Sequel Pro software for data analysis. Additionally, collaboration and word co-occurrence networks were generated using VOSviewer. Results: The total number of documents published between 2008-2016 was 586, of which local authorship (Saudi Arabia) constituted a small share, accounting only for 19.3% (113 documents). Those with foreign authorship (other countries excluding Saudi Arabia) represented 80.7% (473) of the total. Furthermore, the three countries that co-author documents with researchers from Saudi Arabia are Egypt, the United States and the United Kingdom. Likewise, these three countries serve as nodes connecting researchers from other countries located in Asia, Africa, Europe and Latin America. An analysis of the top-five journals that cited the research published revealed that that 90.2% of them belonged to the first and second quartiles confirms the quality of the research being published. Word co-occurrence analysis established a slight shift of focus in the research topics published during the last four years studied, as a new cluster was formed with terms related to "education", "intervention" and "implementation". Conclusion: The journal has managed, in very few years, to be considered by researchers worldwide. Furthermore, throughout the years, the journal showed an evolution in the main topics covered, providing a contemporary overview of public health. Keywords: Bibliometric, Citation analysis, Collaboration network, Journal evaluation